Eucalyptus-Biochar Application for Mitigating the Combined Effects of Metal Toxicity and Osmotic-Induced Drought in Casuarina glauca Seedlings - Oumaima Ayadi; Khawla Tlili; Sylvain Bourgerie; Zoubeir Bejaoui (Land, 2025)
Land degradation from trace metal pollution in North Africa severely compromises soil fertility. This study investigates the synergistic remediation potential of Eucalyptus biochar (EuB) and Casuarina glauca in iron mine soil contaminated with Fe, Zn, Mn, Pb, Cd, and As. Seedlings were grown for six months in: non-mining soil (NMS), contaminated soil (CS), and CS amended with 5% EuB (CS + EuB). Comprehensive ecophysiological assessments evaluated growth, water relations, gas exchange, chlorophyll fluorescence, oxidative stress, and metal accumulation. EuB significantly enhanced C. glauca tolerance to multi-trace metal stress. Compared to CS, CS + EuB increased total dry biomass by 14% and net photosynthetic rate by 22%, while improving predawn water potential (from −1.8 to −1.3 MPa) and water-use efficiency (18%). Oxidative damage was mitigated. EuB reduced soluble Fe by 71% but increased Zn, Mn, Pb, and Cd mobility. C. glauca exhibited hyperaccumulation of Fe, Zn, As, Pb, and Cd across treatments, with pronounced Fe accumulation under CS + EuB. EuB enhanced nodule development and amplified trace metals sequestration within nodules (Zn: +1.4×, Mn: +2.4×, Pb: +1.5×, Cd: +2.0×). The EuB-C. glauca synergy enhances stress resilience, optimizes rhizosphere trace metals bioavailability, and leverages nodule-mediated accumulation, establishing a sustainable platform for restoring contaminated lands.